Domestic Violence and Sexual Assault Service Providers’ Perspectives on Nigerian Immigrants’ Domestic Violence Experiences - Ogbonnaya, Ijeoma Nwabuzor (Violence against women, 2021)
We investigated 13 domestic violence (DV) and sexual assault agency directors’ perspectives regarding Nigerian immigrants’ experiences of violence, DV-related service needs, and best strategies for providing those needs. Directors across five U.S. states were surveyed. Descriptive analyses showed the most common DV types were controlling behavior and cultural/traditional. The most important DV support needs were informational, informal, and legal. Formal support from DV agencies, support groups, and law enforcement was rated the most helpful strategies. Participants wanted to learn more about Nigerian immigrants’ DV experiences. Findings highlight implications for the development of Nigerian-specific DV services.